Synthesis of PF-543 Derivatives Using Simple Synthetic Methods and Their Biological Effect Analysis for the Development of Anticolorectal Cancer Agents - Shrestha, Jitendra; Lee, Joo-Youn; Park, Eun-Young; Baek, Dong J. (Letters in Drug Design & Discovery, 2021)
Background: Sphingolipids, even in extremely low doses, regulate various physiological functions. Particularly, immune and cancer cells might be controlled by changes in the sphingosine- 1-phosphate (S1P) levels, and S1P has been studied for a long time as a major target for new drug development. Sphingosine kinase (SK) phosphorylates sphingosine to produce S1P. An increase in the S1P levels promotes the growth of cancer cells. SK has 2 isoforms, SK1 and SK2, both of which are involved in the growth of cancer cells. Objective: PF-543 has been developed as an SK1 inhibitor and has a non-lipid structure that differs from those of general SK inhibitors. While PF-543 has a potent SK1 inhibitory effect, and has low anticancer activity in some types of cancer cells. Therefore, the development of other PF-543 derivatives is needed. Methods: We designed a structurally simplified derivative of PF-543. To primarily demonstrate that the designed structure was biologically active, 8 derivatives were synthesized by a 2-step method using the commercial starting material, and their biological activities were evaluated. Results: The SK1-inhibitory effects of the synthesized derivatives were not higher than that of PF- 543. However, the anticancer activity and apoptotic effect of the derivatives were similar to those of PF-543, despite their fabrication from a simple modification of the PF-543 structure. In a docking study, the derivatives were found to bind SK1 in a form similar to PF-543. Conclusion: Our analogs, which are similar to PF-543, showed comparable anticancer activity, indicating that the synthesized derivatives are structurally more efficient for anticancer activity than PF-543. Therefore, our study provides important information that may be useful for developing new anticancer substances that target SK1.
Keywords: derivative